DETECTION OF THE PRESENCE OF MICROORGANISMS DURING PRODUCTION OF PLASTERBOARD - Hana Sekavová; Zdeněk Prošek; Pavla Ryparová (Acta Polytechnica CTU Proceedings)
This article is focused on detection microorganisms appearing during production of gypsum plasterboards. The research is carried out within the project TAČR ZÉTA TJ02000235 Sádrokarton se zvýšenou odolností proti bilogické degradaci (Gypsum plasterboard with increased biodegradation resistance). This article shows first part of this issue what was detection of the most critical place of production, where is the highest risk of bacterial contamination and it open the area to find suitable modification of production process or recipes of gypsum plasterboards.